The effect of cesium content on the thermodynamic stability and chemical durability of (Ba, Cs)1.33(Al, Ti)8O16 hollandite. Issue 12 (7th September 2020) - Zhao, Mingyang; Amoroso, Jake W.; Fenker, Kalee M.; DiPrete, David P.; Misture, Scott; Utlak, Stephen; Besmann, Theodore; Brinkman, Kyle
Abstract: Titanate‐based hollandite ceramics are promising nuclear waste forms for Cs immobilization. In this work, a series of Al‐substituted hollandite (Ba, Cs)1.33 (Al, Ti)8 O16 was investigated across a broad compositional range with varying Cs content. Powder X‐ray diffraction showed that all samples exhibited a tetragonal hollandite phase. Enthalpies of formation determined by high‐temperature melt solution calorimetry indicated enhanced thermodynamic stability with increased Cs content, which generally agreed with sublattice‐based thermodynamic calculations. Moreover, enthalpies of formation of the samples were primarily affected by three factors: (a) relative sizes of cations on the A‐sites and B‐sites, (b) tolerance factor, and (c) optical basicity. Fractional element release revealed that Cs retention was significantly improved for the high Cs‐containing hollandite compositions, which were supported by the evolution of microstructure of the pre and postleach particles. Elution studies of Al‐substituted hollandite spiked with radioactive 137 Cs indicated that transmutation of Cs to Ba in the hollandite was accompanied by an increase in the retention of the Cs decay product, suggesting long‐term stability of Al‐substituted hollandite phase.